2022
DOI: 10.1111/ene.15650
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of clinical and neurophysiological features in essential tremor

Abstract: Background and purpose Essential tremor (ET) is a common and heterogeneous disorder characterized by postural/kinetic tremor of the upper limbs and other body segments and by non‐motor symptoms, including cognitive and psychiatric abnormalities. Only a limited number of longitudinal studies have comprehensively and simultaneously investigated motor and non‐motor symptom progression in ET. Possible soft signs that configure the ET‐plus diagnosis are also under‐investigated in follow‐up studies. We aimed to long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 52 publications
4
25
1
Order By: Relevance
“…Thus, our findings of increased sNfL in ET may suggest some common underlying neuro-axonal damage. This is also supported by a recent longitudinal study which showed clinical progression of motor symptoms in ET, namely spread of tremor in multiple body segments and emergence of soft signs, over time [27].…”
Section: Discussionsupporting
confidence: 71%
“…Thus, our findings of increased sNfL in ET may suggest some common underlying neuro-axonal damage. This is also supported by a recent longitudinal study which showed clinical progression of motor symptoms in ET, namely spread of tremor in multiple body segments and emergence of soft signs, over time [27].…”
Section: Discussionsupporting
confidence: 71%
“…It should be also acknowledged, however, that relying on diagnostic codes from GP databases to select incident ET cases might lead to an incorrect diagnosis in approximately 35% to 50% of ET cases, as reported in previous studies [7, 41–44]. This, in turn, might overestimate our results either in terms of undertreatment or in terms of proportion of true ET patients discontinuing the treatment.…”
Section: Discussionmentioning
confidence: 70%
“…First, as previously mentioned, we used a set of diagnostic codes from GP databases to select incident ET cases rather than employing a population-based design. This approach, on the one hand, might underestimate the true disease burden [7], but on the other hand, might lead to an incorrect diagnosis of ET [7,[41][42][43][44]. To avoid these biases, we applied very strict criteria to exclude tremor-related diseases, such as dystonia, ataxia, Parkinson's disease, or parkinsonism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, individuals with ET may exhibit a mild slowing of voluntary movement, often referred to as bradykinesia [2][3][4][5][6][7][8][9][10][11][12][13], and the impaired movement performance cannot be solely attributed to the secondary effects of tremor [3][4][5][6][7][9][10][11]. Furthermore, various studies have documented the presence of cognitive dysfunction in ET patients [2,7,8,[13][14][15][16][17][18][19]. For instance, recent ndings indicate that over 30% [8], and possibly up to 50% of ET patients [7] exhibit mild cognitive impairment (MCI) based on neurophysiological assessments [20,21].…”
Section: Introductionmentioning
confidence: 99%